Parenteral nutrition with a focus on lipid composition: a brief review (Research, Society and Development, 2022)
Parenteral nutrition (PN) aims to provide a mixture of nutrients to patients undergoing treatment, through the venous system, in order to restore their caloric intake and avoid complications. In this case, lipids play a significant role due to their biological functions and their high energy density, which makes them suitable for the recovery of the patient's caloric intake. In NP, lipid emulsions are made from foods rich in essential fatty acids, such as vegetable oils, especially soybean oil, which is a major source of omega-6 fatty acid, olive oil (rich in oleic acid) , and fish oil, source of EPA and DHA. The use of these fatty acids contributes to the complete maintenance of health. Therefore, the objective of the present study was to elaborate a narrative review about the benefits of lipids in the recovery of patients undergoing parenteral nutritional therapy. Platforms including the Web of Science, Google Scholar, Scopus, PubMed, SciELO and Portal Periodicos Capes were used to file the main manuscripts on the subject in question. The results obtained help professionals in the field to provide their patients with the most appropriate lipid emulsion therapy to improve their clinical condition.